Dietary Conjugated Linoleic Acid and Hepatic Steatosis: Species-Specific Effects on Liver and Adipose Lipid Metabolism and Gene Expression - Diwakar Vyas; Anil Kumar G. Kadegowda; Richard A. Erdman (Journal of Nutrition and Metabolism)
Objective. To summarize the recent studies on effect of conjugated linoleic acid (CLA) on hepatic steatosis and hepatic and adipose lipid metabolism highlighting the potential regulatory mechanisms. Methods. Sixty-four published experiments were summarized in which trans-10, cis-12 CLA was fed either alone or in combination with other CLA isomers to mice, rats, hamsters, and humans were compared. Summary and Conclusions. Dietary trans-10, cis-12 CLA induces a severe hepatic steatosis in mice with a more muted response in other species. Regardless of species, when hepatic steatosis was present, a concurrent decrease in body adiposity was observed, suggesting that hepatic lipid accumulation is a result of uptake of mobilized fatty acids (FA) from adipose tissue and the liver's inability to sufficiently increase FA oxidation and export of synthesized triglycerides. The potential role of liver FA composition, insulin secretion and sensitivity, adipokine, and inflammatory responses are discussed as potential mechanisms behind CLA-induced hepatic steatosis.